1997
DOI: 10.1088/0305-4470/30/22/023
|View full text |Cite
|
Sign up to set email alerts
|

Bound-state asymptotic estimates for window-coupled Dirichlet strips and layers

Abstract: We consider the discrete spectrum of the Dirichlet Laplacian on a manifold consisting of two adjacent parallel straight strips or planar layers coupled by a finite number N of windows in the common boundary. If the windows are small enough, there is just one isolated eigenvalue. We find upper and lower asymptotic bounds on the gap between the eigenvalue and the essential spectrum in the planar case, as well as for N = 1 in three dimensions. Based on these results, we formulate a conjecture on the weak-coupling… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 8 publications
0
51
0
3
Order By: Relevance
“…we check that 6) where the constant C is independent of g and δ. In view of the inequality obtained and (2.5) it remains to show that the series…”
Section: Domain Of H ωmentioning
confidence: 99%
See 1 more Smart Citation
“…we check that 6) where the constant C is independent of g and δ. In view of the inequality obtained and (2.5) it remains to show that the series…”
Section: Domain Of H ωmentioning
confidence: 99%
“…The two-dimensional case was studied quite intensively, we refer here to [1], [2], [3], [4], [5], [6], [9] (see also references therein). It was shown that the perturbation by the window(s) is a negative one, i.e., it leads to the presence of the isolated bound states below the essential spectrum; the latter is invariant w.r.t.…”
Section: Introductionmentioning
confidence: 99%
“…Some results were obtained earlier. Namely, variational estimates for the bound state (not for resonances) close to the threshold are in [3,4], for the combined DirichletÄNeumann case are in [8]. Asymptotics of the bound states for the Dirichlet case is in [5,6].…”
Section: Resonances In Coupled Waveguidesmentioning
confidence: 99%
“…However, Exner and Vugalter (1997) used variational techniques to show that for sufficiently small a/d there is just one bound state and that the ground-state eigenvalue, kd, then satisfies (3.18) for some positive c 1 and c 2 . It is clear that for small windows, this will produce values of kd which differ from the upper cut-off by an extremely small amount and this explains why we were unable to compute bound-state energies when a/d is less than about 0.25.…”
Section: Laterally Coupled Planar Waveguidesmentioning
confidence: 99%
“…Exner and Vugalter (1997) considered the case when the hole was sufficiently small so that only one eigenvalue occured below the continuous spectrum. The authors were then able to provide upper and lower asymptotic bounds on the gap between the eigenvalue and the continuous spectrum.…”
Section: Introductionmentioning
confidence: 99%